2013
DOI: 10.1159/000348540
|View full text |Cite
|
Sign up to set email alerts
|

Height Gain at Adult-Height Age in 184 Short Patients Treated with Growth Hormone from Prepubertal Age to Near Adult-Height Age is Not Related to GH Secretory Status at GH Therapy Onset

Abstract: Background: GH release after stimuli classifies short children as severe idiopathic isolated GH deficiency (IIGHD), mild IIGHD, dissociated GH release (DGHR) and normal GH release (NGHR) and anthropometric birth data as adequate for gestational age (AGA) or small for gestational age (SGA). GH release after stimuli classifies AGA patients as IIGHD or as idiopathic short stature (ISS). Aim: To compare height gain induced by GH therapy (31.8 ± 3.5 µg/kg/day, 7.7 ± 1.6 years) started at prepubertal age and stopped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…In the last decades, several prediction models for nFAH in GHD patients treated with GH have been developed [6,16,17,18,19,20,21]. Thomas et al [16] developed a model based on a rather small cohort (n = 61) of Belgian GHD children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decades, several prediction models for nFAH in GHD patients treated with GH have been developed [6,16,17,18,19,20,21]. Thomas et al [16] developed a model based on a rather small cohort (n = 61) of Belgian GHD children.…”
Section: Discussionmentioning
confidence: 99%
“…De Ridder et al [18] analyzed the data of the Dutch growth database and described models for prepubertal and pubertal children at the start and after the first year of GH treatment. Carrascosa et al [19] retrieved data from 184 Spanish children from different medical centers and described a model at the end of the second treatment year as well as a model at the onset of the pubertal growth spurt, predicting the Ht SDS gain to be achieved at adult height age. Blethen et al [20] described a model derived from the Genentech study (n = 121).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GH secretion estimated by GH max peak during provocative tests did not enter the model. Recently, Carrascosa et al (24) found no difference in height gain to adult age among patients with different GH secretion status on GH treatment, including short children born SGA, suggesting that GH secretion estimated during provocative tests are of little help when GH therapy is decided. Considering the benefits of GH treatment and the care with safety issues, these findings reinforce the need of continuous search for the best predictors of growth response and individualization of GH dosing (25).…”
Section: Discussionmentioning
confidence: 99%
“…In a Spanish cohort of 184 children, part of a larger cohort [18] with idiopathic GHD, ISS or SGA, treatment with GH in an average dosage of 32 µg/kg/day up to AH resulted in a similar AH (0.4-0.5 standard deviation (SD) below TH) and AH gain (1.6-1.7 SD), irrespective of diagnosis [19]. In the Netherlands, France and Japan, where generally lower GH doses have been used, average AH was 1.6-2 SD lower than TH [20,21,22].…”
Section: Measures Of Success Of Gh Treatmentmentioning
confidence: 99%